2015
DOI: 10.3389/fnhum.2015.00682
|View full text |Cite
|
Sign up to set email alerts
|

A Behavioral and Electrophysiological Investigation of the Effect of Bilingualism on Lexical Ambiguity Resolution in Young Adults

Abstract: Previous research suggests that bilinguals demonstrate superior cognitive control processes than monolinguals. The goal of the current investigation was to examine whether this “bilingual advantage” is observed in a language processing task that requires inhibition, i.e., lexical ambiguity processing. Monolingual and bilingual participants read sentences that biased the reading of a terminal homonym toward the subordinate or dominant reading (e.g., The doctor asked her to step onto the scale.). A relatedness j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 56 publications
(58 reference statements)
1
21
1
Order By: Relevance
“…Of the 56, 46 were original studies [7,14,21,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69] and 10 were review/meta-analysis studies [70,71,72,73,74,75,76,77,78,79]. The bilingual studies were conducted on several continents, with 23 (41.1%) having been conducted in North America (particularly in Canada) [14,21,27,29,30,31,32,34,38,45,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 56, 46 were original studies [7,14,21,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69] and 10 were review/meta-analysis studies [70,71,72,73,74,75,76,77,78,79]. The bilingual studies were conducted on several continents, with 23 (41.1%) having been conducted in North America (particularly in Canada) [14,21,27,29,30,31,32,34,38,45,…”
Section: Resultsmentioning
confidence: 99%
“…Different tasks have been used to test the bilingual advantage in cognitive control; among them, the Simon task [80], the attention network test [81], Flanker tasks [82], the Stroop task [83], and switching tasks [36] have been most frequently used to test the bilingual advantage in cognitive control. Of the 46 original studies implemented in the present review, 23 used the Simon task, 5 the attention network test, 9 Flanker tasks, 9 the Stroop task, and 7 a switching task; moreover, in 20 original studies, other experimental tasks were used: e.g., verbal fluency [84], interpretation, a judgment task [53], an N-back task [85], a reading task, a picture–word identification task [63], the Wisconsin card sorting test [86], the Tower of London task [87], the digit span task [88], the Hebb repetition paradigm [89], Luria’s tapping task [90], the opposite worlds task [91], the reverse categorization task [92], the sustained attention to response task [93], the trail making test [94], and the dichotic listening task [95]. Please note that some studies used more than one experimental task, and as a result, the total number of experimental tasks is higher than the total number of original studies.…”
Section: Resultsmentioning
confidence: 99%
“…However, with respect to the behavioral results, only on the Stroop task [83] was evidence found in favor of the 'bilingual advantage in cognitive control' hypothesis. Finally, in their EEG study, Kousaie and colleagues [53] found no support for the bilingual advantage on a relatedness judgment task in young adults; the analysis of the behavioral scores revealed that the monolinguals and the bilinguals performed equally well on the task. Only subtle electrophysiological differences in the language processing were found.…”
Section: Neuroimaging Resultsmentioning
confidence: 91%
“…Different tasks have been used to test the bilingual advantage in cognitive control; among them the Simon task [80], the Attention Network Test [81], Flanker tasks [82], the Stroop task [83], and switching tasks [36] have been most frequently used to test the bilingual advantage in cognitive control. Of the 46 original studies implemented in the present review, 23 used the Simon task, 5 the Attention Network Test, 9 Flanker tasks, 9 the Stroop task, and 7 a switching task; moreover, in 20 original studies, other experimental tasks were used: e.g., verbal fluency [84], interpretation, a judgment task [53], an N-back task [85], a reading task, a picture-word identification task [63], the Wisconsin Card Sorting Test [86], the Tower of London task [87], the digit span task [88], the Hebb repetition paradigm [89], Luria's tapping task [90], the Opposite Worlds task [91], the reverse categorization task [92], the Sustained Attention to Response task [93], the Trail Making test [94], and the Dichotic listening task [95]. Please note that some studies used more than one experimental task, and as a result, the total number of experimental tasks is higher than the total number of original studies.…”
Section: General Resultsmentioning
confidence: 99%
See 1 more Smart Citation